Marginal structural models and other analyses allow multiple estimates of treatment effects in randomized clinical trials: meta-epidemiological analysis - Ewald, H; Speich, B; Ladanie, A; Bucher, H; Ioannidis, J; Hemkens, L (Elsevier, 2018)
Objective To determine how marginal structural models (MSMs), which are increasingly used to estimate causal effects, are used in randomized clinical trials (RCTs) and compare their results with those from intention-to-treat (ITT) or other analyses. Design and Setting We searched PubMed, Scopus, citations of key references, and Clinicaltrials.gov. Eligible RCTs reported clinical effects based on MSMs and at least one other analysis. Results We included 12 RCTs reporting 138 analyses for 24 clinical questions. In 19/24 (79%), MSM-based and other effect estimates were all in the same direction, 22/22 had overlapping 95%CIs, and in 19/22 (86%), the MSM-effect estimate lay within all 95%CIs of all other effects (in two cases no CIs were reported). For the same clinical question, the largest effect estimate from any analysis was 1.19-fold (median; IQR 1.13-1.34) larger than the smallest. All MSM and ITT-effect estimates were in the same direction and had overlapping 95% CIs. In 71% (12/17), they also agreed on the presence of statistical significance. MSM-based effect estimates deviated more from the null than those based on ITT (p=0.18). The effect estimates of both approaches differed 1.12-fold (median; IQR 1.02-1.22). Conclusions MSMs provided largely similar effect estimates as other available analyses. Nevertheless, some of the differences in effect estimates or statistical significance may become important in clinical decision-making and the multiple estimates require utmost attention of possible selective reporting bias.